EFEKTIVITAS KESEJAHTERAAN DALAM MENINGKATKAN KINERJA GURU DI SMP INFORMATIKA DAN TAHFIDZ ADZIKRA SAWANGAN, DEPOK, JAWA BARAT - Sodikin, Didik; susanto, Susanto; Tanrere, Syamsul Bahri (MPP: Lembaga Penelitian Dan Studi Kebijakan, 2024)
This research aims to analyze and describe teacher performance, teacher welfare and find the effectiveness of welfare in improving teacher performance at SMP Informatika and Tahfidz Adzikra Sawangan, Depok, West Java.The conclusions of this research are first, regarding teacher performance, overall a teacher's performance can be said to be good, this can be seen based on several indicators such as indicators for making Learning Implementation Plans, indicators for Preparing Teaching Materials, Indicators for Innovation in Effective Learning Activities, Indicators Selection of Learning Media and Discipline Indicators. Second, so far teacher welfare to improve teacher performance at Informatics and Tahfidz Adzikra Middle Schools has been implemented as closely as possible, this can be seen in accordance with welfare indicators which include: Salary, Providing Rewards, Providing opportunities to improve teaching abilities, Comfortable working environment conditions, welfare The honorary teacher at SMP Informatika and Tahfidz Adzikra Sawangan, Depok, from a financial perspective, is not very large when compared to superior schools out there, because this school is still relatively new, and there are still very few students at the school. Honorary teachers who feel appreciated, supported and have good working conditions will tend to be more motivated, enthusiastic and dedicated in providing the best education for students.Third, the provision of welfare to teachers makes a big contribution to improving the performance of teachers at SMP Informatika and Tahfidz Adzikra Sawangan, Depok City. This can be seen when teachers' salaries are increased, teachers look enthusiastic, this means that welfare has a big influence on the performance of teachers. , because welfare can provide encouragement to employees to produce maximum performance